Pelatihan Peningkatan Literasi Keuangan dan Pengelolaan Keuangan Rumah Tangga di Desa Tanimulya - Rifka Agustianti; Deni Ramdhani; Rahmi Mudia Alti; Yoana Nurul Asri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This service activity is in collaboration with a group of women from Tanimulya village. The partners of this service activity encounter several problems related to financial management: imbalance between income and expenses, inability to determine family financial priorities, weakness in planning expenses, weakness in recording, lack of control over spending, tendency to is more about consumption behavior than investment. The proposed solution to this problem is to establish a training program for mothers on how to plan and manage family finances effectively and efficiently, which in turn can improve family happiness. family. As part of this activity, awareness-raising materials and activities were provided on financial literacy, family income and expenditure budget planning (APBK), understanding of financial industry products and digital financial planning applications, as well as a call to change consumer behavior trends into investment trends. This activity was carried out in the village of Tanimulya, with the participation of staff from the Community Services Team of Nurtanio University in Bandung. After carrying out service activities, it is desirable to achieve the goals of the activity, which are: Raise awareness and understanding of the importance of household financial records, the function and role of financial records in balancing income and expenditure of household funds and foster a sense of responsibility in doing business. family financial management, to raise awareness of the importance of saving and investing in households. Evaluation of service activities is carried out at the end of the activity using a questionnaire and results are given using pre-test and post-test evaluations. Based on the pre- and post-test results, participants increased their knowledge and understanding of the material presented. The activities were able to run smoothly thanks to the enthusiasm and enthusiasm of the participants.